Comorbidities in Headache Disorders - Giamberardino, Maria Adele; Martelletti, Paolo (Springer International Publishing : Imprint: Springer, 2017)
This book provides up-to-date information on all aspects of the comorbidities that are associated with the headache disorders commonly seen in the primary care and hospital settings, including migraine, tension-type headache, and cluster headache. The coverage is wide ranging and encompasses all of the well-established comorbidities: cardio- and cerebrovascular disease, psychiatric conditions, epilepsy, sleep disorders, and various pain disorders, such as visceral pain, fibromyalgia, orofacial pain, and neuropathic pain. Individual chapters are also devoted to obesity and other metabolic comorbidities and to the comorbidities associated specifically with pediatric headaches. The information provided will assist readers in understanding the complex relationships between headache disorders and these various conditions and in delivering effective care that reflects the latest knowledge. The book is designed to meet the daily practice needs of general physicians, general neurologists, clinical psychologists, neurologists in training, and medical students. It is published as part of the series Headache, which is endorsed by the European Headache Federation - EHF.
Keywords: Medicine.; Internal medicine.; Rheumatology.; Neurology.; Otorhinolaryngology.; Pain medicine.; Psychiatry.; elektronické knihy; electronic books